Exercise Therapy Pada Perawatan Chronic Low Back Pain: Scoping Review - Brigitta; Holil, Levana; Anggraini, Wita; Sulistyowati, Indrani; Putri Ariyani, Annisaa (Jurnal Kedokteran Gigi Terpadu, 2025)
Background: Chronic low back pain (CLBP) is a major problem for dentists due to high visual demands that result in postural adaptations. One of the treatment options is exercise therapy, which consists of physical activity that aims to relieve pain. Objectives: This scoping review discusses exercise therapy methods and outcomes in patients with chronic low back pain. Methods: This scoping review is guided by PRISMA-ScR. The literature search method used PCC and article searches using PubMed and Google Scholar, which obtained 10,773 journals. 19 journals were selected according to the inclusion criteria, including: stretching exercises in the form of proprioceptive neuromuscular facilitation (n=3), pilates (n=3), core stabilisation exercises (n=4), aerobic exercise (n=1), yoga (n=2), and journals that compared more than one exercise therapy (n=6). Results: The results of this scoping review show that exercise therapy is effective for CLBP patients to reduce pain. It can also improve functional ability, quality of life, muscle strength, muscle endurance, range of motion, balance, flexibility, and spinal stability. Conclusion: Exercise therapy can be the main option for the treatment of CLBP patients.